An Investigation on the Free Vibration Behaviors of Additively Manufactured PA6 Layered Plates: Influences of Stacking Sequence, Infill Ratio, and Boundary Conditions (Fracture and Structural Integrity, 2025)
This study investigates the free vibration behavior of 3D-printed PA6 layered plates by considering the effects of stacking sequence, infill ratio, and boundary conditions. Unlike previous works, this research provides a comprehensive analysis combining experimental pre-analyses and finite element simulations. Nine different plate configurations with infill ratios of 40%, 70%, and 100%, and aspect ratios (a/b = 1, 1.5, 2, and 2.5) were analyzed under clamped and simply supported boundary conditions. The mechanical properties of the printed material were determined through tensile testing, and these properties were used as input for the numerical model developed in ANSYS. Before the vibration analyses, the model was validated by comparing its results with existing literature, showing close agreement. Results showed that higher infill ratios in the outer layers increase natural frequencies due to improved stiffness, whereas a denser core can reduce them due to increased mass. Additionally, increasing the aspect ratio leads to higher natural frequencies. The findings offer valuable insights for improving the vibration performance of 3D-printed PA6 components used in functional parts such as gears, fan blades, and robotic arms.
Keywords: Polyamides; Fused filament fabrication; Stacking sequence; Infill ratio,; Natural frequency; Finite element methods